The clinical utility and prognostic value of next-generation sequencing for measurable residual disease assessment in acute myeloid leukemia - Yu Liu; Huanchen Cheng; Meng Sun; Tiejun Gong; Jun Ma (Therapeutic Advances in Hematology, 2025)
Background: Next-generation sequencing (NGS) offers a method for measurable residual disease (MRD) assessment by detecting leukemia-associated genetic mutations. Objective: This study aimed to evaluate the clinical implications and prognostic value of NGS-based MRD assessment in acute myeloid leukemia (AML). Design: Sixty-nine adult AML patients were included for NGS (targeted sequencing of AML-related 47 genes), of which 56 patients at initial diagnosis, 69 patients in the first day of consolidation therapy (C1D1), and 51 patients during 2-year MRD monitoring (detection following the C1D1) were enrolled. Methods: Mutation data were categorized into gene mutations, somatic mutations and somatic mutations excluding clonal hematopoiesis of indeterminate potential (CHIP) for analysis. The study also integrated multiparameter flow cytometry (MFC) and NGS data at C1D1 to evaluate the prognostic significance of combining the two MRD techniques. Results: Mutation detection rates were 98.21%, 69.57%, and 84.31% for AML patients at initial diagnosis, C1D1 stage, and MRD monitoring, respectively, identified by targeted sequencing. During MRD monitoring, the ETV6 mutation frequency was significantly higher in relapsed patients than in non-relapsed patients ( p < 0.05). The mean variant allele frequency (VAF) was significantly higher in the 2-year MRD monitoring period (0.160 ± 0.155) compared to the C1D1 period (0.058 ± 0.087; p < 0.05) in relapsed patients. Survival analysis revealed that patients with a mean VAF (somatic mutations excluding CHIP) ⩽0.004 in the C1D1 stage and ⩽0.020 during MRD monitoring had a better prognosis. Furthermore, the combination of MFC and NGS-based MRD (somatic mutations excluding CHIP) at C1D1 stage showed that patients who were negative for two tests had longer survival than those who were negative for only one. Conclusion: The combined assessment of MFC-MRD and NGS-MRD status provides a refined prognostic stratification, with the absence of somatic mutations and MFC-MRD negativity correlating with improved progression-free survival, which is expected to improve clinical prognostic assessment of AML patients.